Asia-Pacific Countries with Special Needs Development Report 2017 - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 2017)
The Asia-Pacific countries with special needs development report 2017 introduces the access to physical infrastructure index as a tool to capture the multidimensional character of infrastructure and to illustrate the strong positive causality between infrastructure and sustainable development. The report highlights that significant infrastructure gaps exist among the countries with special needs, and estimates that these countries need to invest an average of 10.5 per cent of GDP per annum in infrastructure development and maintenance to close the infrastructure deficit, taking population growth, increasing urbanization and the impact of climate change into account. Such investment far exceeds current levels of infrastructure funding. Given the limited resource availability in countries with special needs, the report emphasizes that clear priorities are required for infrastructure development and that sequencing infrastructure investment is necessary by determining where the impact of additional infrastructure on sustainable development outcomes may be the largest.